Greater Britain and the Great War: British and New Zealand official propaganda in the First World War - Hynes, G (2019)
Propaganda of the First World War has been a persistent area of interest for historians. The national focus of much of the historiography of the war has, however, left significant gaps in understanding. This thesis examines an important area of elision: propaganda between Britain and the settler Dominions of Canada, Australia, New Zealand, South Africa, and Newfoundland, which this thesis terms ‘Greater British Propaganda.’